PELINDUNGAN HUKUM BAGI PASANGAN DALAM PERKAWINAN TIDAK TERCATAT (SIRI) TERKAIT KEPEMILIKAN HARTA BENDA - Devi Syalwa Syahfitri; Juni Kristiani Meliala; Petrus Medikson Pardede; Suci Rohani Panjaitan; Vany Helpiana Saragih; Parlaungan Siahaan (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This study examines the legal protection of property ownership for couples in unregistered (siri) marriages and compares it with the legal framework governing officially registered marriages. Unregistered marriages often lead to legal uncertainty, particularly regarding shared property in cases of divorce or inheritance. The absence of official registration weakens the legal standing of such unions, increasing the risk of injustice, especially for women. Existing legal provisions do not explicitly regulate property protection in unregistered marriages, leaving their resolution largely dependent on law enforcement interpretation or case-by-case court decisions. This research adopts a normative-empirical approach by analyzing statutory regulations and collecting empirical data from field observations and interviews. The findings indicate that marriage registration is crucial for ensuring legal protection of jointly acquired property. Isbat nikah (marriage validation) and the principles of contract law serve as alternatives for gaining legal recognition. This study aims to contribute to the development of a more just and adaptive legal protection system for couples in unregistered marriages.